2013
DOI: 10.1002/app.39035
|View full text |Cite
|
Sign up to set email alerts
|

Metallocene polypropylene crystallization kinetic during cooling in rotational molding thermal condition

Abstract: is an open access repository that collects the work of Arts et Métiers ParisTech researchers and makes it freely available over the web where possible. ABSTRACT: This article is part of an ambitious project. The aim is to simulate mechanical properties of rotomolded part from microstructure consideration. Main objective here is to consider metallocene polypropylene crystallization kinetic (PP) during cooling stage in rotational molding. Crystallization kinetic of metallocene PP is so rapid that microscopy cann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 62 publications
0
9
0
Order By: Relevance
“…However, taking into consideration that SS catalysts are suitable only for olefin polymerization; it is clear that these materials contribute minimally. Different grades of PE [24,[97][98][99][100][101] and PP [102] have, nonetheless, demonstrated their suitability to the RM process. For instance, experiments by Xin et al [98] and later by Hay et al [97] showed that under similar molding conditions SS PEs possessed; better mechanical properties, wider processing windows and higher bubble dissolution rates at lower temperatures than ZN catalyzed polymers.…”
Section: Single Site Polymersmentioning
confidence: 99%
“…However, taking into consideration that SS catalysts are suitable only for olefin polymerization; it is clear that these materials contribute minimally. Different grades of PE [24,[97][98][99][100][101] and PP [102] have, nonetheless, demonstrated their suitability to the RM process. For instance, experiments by Xin et al [98] and later by Hay et al [97] showed that under similar molding conditions SS PEs possessed; better mechanical properties, wider processing windows and higher bubble dissolution rates at lower temperatures than ZN catalyzed polymers.…”
Section: Single Site Polymersmentioning
confidence: 99%
“…A previous article described a thermal model (1D) that simulates evolution of polymer temperature during processing. This model was based on finite differences method using a centered implicit scheme for space and a decentred implicit scheme for time.…”
Section: Theoretical Backgroundmentioning
confidence: 99%
“…Equations and interfaces were treated with the same system. Calculated results from this thermal model were computed using Matlab with the assumptions described before …”
Section: Theoretical Backgroundmentioning
confidence: 99%
See 2 more Smart Citations